PENINGKATAN KARAKTER SISWA MELALUI PENGEMBANGAN BUKU AJAR BAHASA INGGRIS INTERAKTIF BERBASIS NILAI-NILAI BUDAYA BANGSA - Marsuki, Marsuki; Efendy, Boby Ardiyanzah (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2015)
The study aims at developing a nation character and culture values-based interactive English textbook and examining its effectivity for the elementary school students in Malang. The development and experiment designs are used and the subjectsÂ consist of experts and target. The expert is an expert in instructional materials and multimedia, while the target is students of the sixth grade Elementary School Dinoyo IV Malang which totals 40 students. The true experiment design, pretest-posttest control group is usedÂ by random sampling technique to obtain experiment and control groups, each of which consists of 20 students. The instruments are questionnaire, interview, and test. Based on the data analysis, it was found that the interactive English textbook fulfilled good criteria of textbook in either material coverage and selection or multimedia application. The positive responses of the students and teachers indicated good quality of textbook in improving studentsâ€™ competences in English. Through statistical test, it was found t result (5.93)Â was bigger than t table (1.310) in level of significance 0.01 and (1.697) in level of significance 0.05. It means that Ha which states â€œThe students of class VIB Elementary School Dinoyo IV Malang who were taught using the nation character and culture values-based interactive English textbook, had better English competences than those of class VIA who were taught using manual English textbookâ€ was accepted, while H0 was rejected. Therefore, it can be concluded that theÂ use of the textbook is very effective in improving the students English competences of Elementary School in Malang.